ChemInform Abstract: The Effect of Chemical Pressure on the Structure and Properties of A2CrOsO6 (A: Sr, Ca) Ferrimagnetic Double Perovskite. Issue 27 (16th June 2016) - Morrow, Ryan; Soliz, Jennifer R.; Hauser, Adam J.; Gallagher, James C.; Susner, Michael A.; Sumption, Michael D.; Aczel, Adam A.; Yan, Jiaqiang; Yang, Fengyuan; Woodward, Patrick M.
Abstract: The ordered double perovskites Sr2 CrOsO6 (I) and Ca2 CrOsO6 (II) are prepared by solid state reaction of stoichiometric amounts of SrO or CaO, CrO3, and Os (Al tube in silica ampoule with PbO2 as O2 source, 950 °C (II)/1000 °C (I), 2 d).